Judicial review and American conservatism : Christianity, public education, and the federal courts in the Reagan era / Robert Daniel Rubin. - Rubin, Robert Daniel (Cambridge historical studies in American law and society., 2017)
The Christian Right of the 1980s forged its political identity largely in response to what it perceived as liberal 'judicial activism'. Robert Daniel Rubin tells this story as it played out in Mobile, Alabama. There, a community conflict pitted a group of conservative evangelicals, a sympathetic federal judge, and a handful of conservative intellectuals against a religious agnostic opposed to prayer in schools, and a school system accused of promoting a religion called 'secular humanism'. The twists in the Mobile conflict speak to the changes and continuities that marked the relationship of 1980s' religious conservatism to democracy, the courts, and the Constitution. By alternately focusing its gaze on the local conflict and related events in Washington, DC, this book weaves a captivating narrative. Historians, political scientists, and constitutional lawyers will find, in Rubin's study, a challenging new perspective on the history of the Christian Right in the United States.